IMPLEMENTASI KURIKULUM MERDEKADALAM MENINGKATKAN MUTU PENDIDIKAN DI RA AN NAHL - Suryani, Yani (Gapenas Publisher, 2024)
Implementation of the Merdeka curriculum at Raudhotul Athfal (RA) An Nahl in order to carry out the mandate of KMA Number 450 of 2024 concerning Guidelines for Curriculum Implementation at Raudhotul Athfal, Madrasah Ibtidaiyah, Madrasah Tsanawiyah Madrasah Aliyah, and Vocational Madrasah Aliyah. How the Merdeka Curriculum is implemented, and what obstacles are found during its implementation is an interesting thing to analyze and study. Data obtained from this research was done by direct observation, interviews and documentation. The results of this research show that the Merdeka curriculum has been running and being implemented. This can be seen from the learning achievements, Learning Implementation Plans (RPP)/teaching modules, assessments carried out and the implementation of the Pancasila and Rahmatan Lil Alamin Student Profile Strengthening Project (P5RA). The implementation of the Independent Curriculum is not free from obstacles, but efforts are still being made to increase competence and knowledge about the Independent Curriculum in conditions of limitations. Lifelong learning does not only apply to students, but teachers also remain enthusiastic about learning. We hope that the government will continue to strive to provide easy access to offline and online learning for teachers, including RA teachers